Rural productivity alternatives from earthen construction: transition to autonomy in deep Colombia - Freddy Diaz Diaz (Vitruvio: International Journal of Architectural Technology and Sustainability, 2025)
The historical conditions of marginality and inefficient state presence in Colombia’s deep rural areas have led peasant communities to explore local productivity alternatives that promote autonomy and social cohesion. In this search, productive projects based on local knowledge, such as those associated with traditional construction, should emerge. This article reflects on rural productivity alternatives explored during a series of awareness-raising workshops on earth as a construction material developed with rural communities in four Colombian municipalities: Icononzo, Agua de Dios, Pasca and Tipacoque. The results show that local communities possess knowledge that has been set aside over time by the different models and paradigms imposed by modernity. This knowledge can become a valuable resource in the search for autonomy and good living in remote rural communities. In conclusion, construction with earth is presented not only as an opportunity for individual habitat improvement, but also as a viable and sustainable productive community alternative.